2020
DOI: 10.36680/j.itcon.2020.019
|View full text |Cite
|
Sign up to set email alerts
|

Change management practices for adopting new technologies in the design and construction industry

Abstract: The architecture, engineering, and construction (AEC) industry has often been accused of being slow to adopt change. Yet the breadth of available technology solutions in the modern AEC industry continues to grow. Companies therefore must be adept at organizational change management; otherwise, the full benefits of technology solutions may never be realized when a company fails to achieve successful change adoption. The objective of this study was to identify the relationships between specific change management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…However, the obstacles are not clearly distinguished and the mechanism of adjusting the culture and strategy is rather abstract. In other studies, internal upper management support was found to a prominent factor (Chung and Choi, 2018 ; Lu et al, 2018 ; Mohtaramzadeh et al, 2018 ; Maali et al, 2020 ; Ukobitz, 2020 ). Furthermore, awareness of the state of affairs in the organization's external environment was found to be essential (Mohtaramzadeh et al, 2018 ; Vaishnavi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…However, the obstacles are not clearly distinguished and the mechanism of adjusting the culture and strategy is rather abstract. In other studies, internal upper management support was found to a prominent factor (Chung and Choi, 2018 ; Lu et al, 2018 ; Mohtaramzadeh et al, 2018 ; Maali et al, 2020 ; Ukobitz, 2020 ). Furthermore, awareness of the state of affairs in the organization's external environment was found to be essential (Mohtaramzadeh et al, 2018 ; Vaishnavi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 80%
“…Organizational changes could be due to merging and acquisition, or cultural, structural, procedural, and technological changes (Smith, 2002 ). Organizational change management is about taking action toward a defined state through practices that are different from the routine practices (Burnes, 2009 ; Maali et al, 2020 ) to reach a goal. The goal of technology change is to offer better products and services through replacing the existing with the new technology (Aremu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations